2019
DOI: 10.1371/journal.pcbi.1006925
|View full text |Cite
|
Sign up to set email alerts
|

Colony entropy—Allocation of goods in ant colonies

Abstract: Allocation of goods is a key feature in defining the connection between the individual and the collective scale in any society. Both the process by which goods are to be distributed, and the resulting allocation to the members of the society may affect the success of the population as a whole. One of the most striking natural examples of a highly successful cooperative society is the ant colony which often acts as a single superorganism. In particular, each individual within the ant colony has a “communal stom… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…On its way back to the nest, it may communicate about its discovery by laying a stronger chemical trail and therefore encourage intranidal workers to visit the same food. Extranidal workers may continue foraging, depending on their ability to transfer their load to other congeners [43,44,47]. Our model suggests that the collective foraging strategies adopted in response to nutritional deficiencies originated from the trail-laying behavior of workers returning to the nest loaded with food.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…On its way back to the nest, it may communicate about its discovery by laying a stronger chemical trail and therefore encourage intranidal workers to visit the same food. Extranidal workers may continue foraging, depending on their ability to transfer their load to other congeners [43,44,47]. Our model suggests that the collective foraging strategies adopted in response to nutritional deficiencies originated from the trail-laying behavior of workers returning to the nest loaded with food.…”
Section: Discussionmentioning
confidence: 94%
“…Our final experiment demonstrated that, even if the collective decision depended initially on the extranidal workers' own nutritional state, this decision could be strengthened or reversed depending on the nutritional state of the recruited intranidal workers. Recently, it has been shown that heterogeneity in crop contents can be relatively high within a colony, even if the foods collected by each forager are distributed via repeated mouth-to-mouth exchange to almost every ant in the colony [47]. It follows that individuals have the potential to reach their individual intake targets by soliciting food from a range of ants in the colony [47].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While it has shed light on regulatory mechanisms of a single carbohydrate-based food source (Greenwald, Baltiansky, and Feinerman, 2018), it is not suitable for studying the simultaneous flows of several food types. To study dynamics of mixing and differential dissemination of several food sources with data from the previous method, assumptions had to be made regarding the homogenization of food in the crop (Greenwald, Eckmann, and Feinerman, 2019). We introduced the ability to directly track two fluorescent dyes.…”
Section: Accepted Articlementioning
confidence: 99%
“…The chosen fluorophores were Rhodamine B (λ ex 533 nm, λ em 627 nm) (used in Greenwald, Segre, and 143 Feinerman, 2015;Greenwald, Baltiansky, and Feinerman, 2018;Greenwald, Eckmann, and Feinerman, 2019),…”
mentioning
confidence: 99%